The Role of Gerak Selasar in Strengthening Children’s Digital Literacy in Samarinda City - Islamu Syiffa; Zulkifli Abdullah (Citra Media Publishing, 2026)
The development of digital technology has brought major changes to education, but the digital literacy gap persists at the elementary school level, especially in rural areas. Children are required to have technological skills and internet ethics from an early age, while the infrastructure, curriculum, and teacher capacity remain inadequate. This condition underscores the importance of research on children’s digital literacy as a foundation for the development of smart, ethical digital citizens. This study aims to analyze the role of Gerak Selaras in improving the digital literacy of elementary school children in Samarinda through the Selaras Mengajar program. The study uses a qualitative case study design through interviews, observations, and documentation. The analysis was conducted to understand the strategies, participation, and social values underlying community activities. The results show that Gerak Selaras plays a significant role in building contextual digital literacy through the development of a locally-based curriculum, the application of participatory methods, and the support of volunteers and partners. Despite resource and funding limitations, the values of solidarity and cooperation are the movement’s main strengths in sustaining itself. This research confirms that Gerak Selaras is a community education model that bridges the digital literacy gap among children and contributes to the development of collaborative policies towards inclusive and sustainable digital education.